2018
DOI: 10.1089/vim.2017.0157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Burden Related to Genital Warts in India

Abstract: The prevalence of genital warts (GW) and self-reported human papillomavirus (HPV) as well as disease-related psychosocial impact among male and female patients aged 18-60 years in India were assessed. GW prevalence was estimated using a 2-week daily log of patients examined from June 7-September 22, 2011 by 200 participating physicians in 6 regions of India. Psychosocial impact was estimated using one-time, self-administered surveys, including HPV Impact Profile (HIP), Cuestionario Específico para Condiloma Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Data regarding the prevalence of genital lesions in men from low/middle income countries are scarce [ 1 , 24 26 ]. These studies used different epidemiological and analytical methodologies, which could explain the differences in prevalence: 5.25% in Peru [ 1 ], 1.22% in India [ 24 ] and 1.99% in Mexico [ 25 ]. The incidence reported in Mexico was 42%, and that in Brazil was 31.9% over a period of four years [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the prevalence of genital lesions in men from low/middle income countries are scarce [ 1 , 24 26 ]. These studies used different epidemiological and analytical methodologies, which could explain the differences in prevalence: 5.25% in Peru [ 1 ], 1.22% in India [ 24 ] and 1.99% in Mexico [ 25 ]. The incidence reported in Mexico was 42%, and that in Brazil was 31.9% over a period of four years [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative incidence was expressed as a percent and also as a rate per 100,000 persons. A weighted estimate of the number of patients with GW in Peru in one year was calculated by dividing the number of cases seen per specialty by the number of providers in that specialty in the physician sample, dividing that by ten (number of days of the daily log) and multiplying it by the number of providers in that specialty in the country and by the total number of workdays in a year (260) minus the average number of non-working days in Peru (12). Annual GW cumulative incidence was calculated in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…This two-week time period has been used in other GW epidemiology studies. 12,13 Physicians recorded the number of patients seen for all causes, the age and gender of each patient, the number of patients seen for a new or existing GW episode, and the number of GW patients retained for treatment versus referred to another provider for treatment or follow-up. The second part of the study involved a self-administered survey of diagnosis patterns in the management of GW.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of GW patients referred to clinics during the study period was estimated using the adjusted multiplier method, separated by the medical specialty, as follows: 42.3% for general practitioners, 31% for dermatologists, 12.6% for gynecologists 7.6% for midwives, 3.6% for urologists, and 1.4% for infectious disease specialists. A study conducted in India reported that most people with GW were referred to dermatologists (18). However, similar studies conducted in South Korea and Taiwan showed that most GW patients were referred to gynecologists (19,20).…”
Section: Discussionmentioning
confidence: 99%